Resisted sprint training with partner towing improves explosive force and sprint performance in young soccer players- a pilot study - Chaalali, Anis; Bouriel, Khalil; Rouissi, Mehdi; Chtara, Moktar; Mkaouer, Bessem; Cronin, John; Chaouachi, Anis; Chamari, Karim (Biology of Sport, 2022)
The purpose of this study was to examine the effects of non-resisted (NRS) and partner-towing resisted (RS) sprint training on legs explosive force, sprint performance and sprint kinematic parameters. Sixteen young elite soccer players (age 16.6 ± 0.2 years, height 175.6 ± 5.7 cm, and body mass 67.6 ± 8.2 kg) were randomly allocated to two training groups: resisted sprint RS (n = 7) and non-resisted sprint NRS (n = 9). The RS group followed a six-week sprint training programme consisting of two “sprint training sessions” per week in addition to their usual soccer training. The NRS group followed a similar sprint training programme, replicating the distances of sprints but without any added resistance. All players were assessed before and after training: vertical and horizontal jumping (countermovement jump (CMJ), squat jump (SJ), and 5-jump test (5JT)), 30 m sprint performance (5, 10, and 20 m split times), and running kinematics (stride length and frequency). In the RS group significant (p < 0.05) changes were: decreased sprint time for 0–5 m, 0–10 m and 0–30 m (-6.31, -5.73 and -2.00%; effect size (ES) = 0.70, 1.00 and 0.41, respectively); higher peak jumping height (4.23% and 3.59%; ES = 0.35 and 0.37, for SJ and CMJ respectively); and 5JT (3.10%; ES = 0.44); and increased stride frequency (3.96%; ES = 0.76). In the NRS group, significant (p < 0.05) changes were: decreased sprint time at 0–30 m (-1.34%, ES = 0.33) and increased stride length (1.21%; ES = 0.17). RS training (partner towing) for six weeks in young soccer players showed more effective performances in sprint, stride frequency and lower-limb explosive force, while NRS training improved sprint performance at 0–30 m and stride length. Consequently, coaches and physical trainers should consider including RS training as part of their sprint training to ensure optimal sprint performance.